Antinociceptive and Antioxidant Activities of Phytol In Vivo and In Vitro Models. (11th June 2013) - Santos, Camila Carolina de Menezes Patrício; Salvadori, Mirian Stiebbe; Mota, Vanine Gomes; Costa, Luciana Muratori; de Almeida, Antonia Amanda Cardoso; de Oliveira, Guilherme Antônio Lopes; Costa, Jéssica Pereira; de Sousa, Damião Pergentino; de Freitas, Rivelilson Mendes; de Almeida, Reinaldo Nóbrega
Abstract : The objective of the present study was to evaluate the antinociceptive effects of phytol using chemical and thermal models of nociception in mice and to assess its antioxidant effects in vitro . Phytol was administered intraperitoneally (i.p.) to mice at doses of 25, 50, 100, and 200 mg/kg. In the acetic acid-induced writhing test, phytol significantly reduced the number of contortions compared to the control group (P < 0.001 ). In the formalin test, phytol reduced significantly the amount of time spent in paw licking in both phases (the neurogenic and inflammatory phases), this effect being more pronounced in the second phase (P < 0.001 ). Phytol also provoked a significant increase in latency in the hot plate test. These antinociceptive effects did not impaire the motor performance, as shown in the rotarod test. Phytol demonstrated a strong antioxidant effect in vitro in its capacity to remove hydroxyl radicals and nitric oxide as well as to prevent the formation of thiobarbituric acid reactive substances (TBARS). Taken as a whole, these results show the pronounced antinociceptive effects of phytol in the nociception models used, both through its central and peripheral actions, but also its antioxidant properties demonstrated in the in vitro methods used.